The acute effects of endurance exercise on epithelial integrity of the airways in athletes and non-athletes: A systematic review and meta-analysis - Pourmanaf, Hadi; Nikoukheslat, Saeid; Sari-Sarraf, Vahid; Amirsasan, Ramin; Vakili, Javad; Mills, Dean E. (Respiratory medicine, 2023)
Acute endurance exercise may induce airway epithelium injury. However, the response of epithelial integrity markers of the airways including club cell secretory protein (CC16) and surfactant protein D (SP-D) to endurance exercise have not been systematically reviewed. Therefore, the aim of this systematic review and meta-analysis was to assess the acute effects of endurance exercise on markers of epithelial integrity of the airways (CC16, SP-D and the CC16/SP-D ratio) in athletes and non-athletes. A systematic search was performed utilizing PubMed/Medline, EMBASE, Web of Science, and hand searching bibliographies of retrieved articles through to September 2022. Based on the inclusion criteria, articles with available data about the acute effects of endurance exercise on serum or plasma concentrations of CC16, SP-D and CC16/SP-D ratio in athletes and non-athletes were included. Quality assessment of studies and statistical analysis were conducted via Review Manager 5.4 software. The search resulted in 908 publications. Finally, thirteen articles were included in the review. Acute endurance exercise resulted in an increase in CC16 (P = 0.0006, n = 13) and CC16/SP-D ratio (P = 0.005, n = 2) whereas SP-D (P = 0.47, n = 3) did not change significantly. Subgroup analysis revealed that the type (P = 0.003), but not the duration of exercise (P = 0.77) or the environmental temperature (P = 0.06) affected the CC16 response to endurance exercise. Acute endurance exercise increases CC16 and the CC16/SP-D ratio, as markers of epithelial integrity, but not SP-D in athletes and non-athletes. •Acute endurance exercise resulted in an increase in CC16 and CC16/SP-D.•SP-D did not change significantly.•The type of exercise affected the CC16 response.•The duration of exercise or the temperature did not affect the CC16 response.